Genetic and developmental analysis of polytene section 17 of the X chromosome of Drosophila melanogaster. - Eberl, D.F.; Perkins, L.A.; Engelstein, M.; Hilliker, A.J.; Perrimon, N. (Genetics, 1992)
Polytene section 17 of the X chromosome of Drosophila melanogaster, previously known to contain six putative lethal complementation groups important in oogenesis and embryogenesis, has here been further characterized genetically and developmentally. We constructed fcl+Y, a duplication of this region, which allowed us to conduct mutagenesis screens specific for the region and to perform complementation analyses (previously not possible). We recovered 67 new lethal mutations which defined 15 complementation groups within Df(1)N19 which deletes most of polytene section 17. The zygotic lethal phenotypes of these and preexisting mutations within polytene section 17 were examined, and their maternal requirements were analysed in homozygous germline clones using the dominant female sterile technique. We present evidence that an additional gene, which produces two developmentally regulated transcripts, is located in this region and is involved in embryogenesis, although no mutations in this gene were identified. In this interval of 37 to 43 polytene chromosome bands we have defined 17 genes, 12 (71%) of which are of significance to oogenesis or embryogenesis.